Progresses in Nanopores Fabrications and Nanopore Sequencing - Kumar, Shruti; K. Agrawal, Yadvendra (Nanoscience & Nanotechnology-Asia, 2011)
Nanopore sequencing technique is gaining tremendous importance as it provides fast and cost effective results. Nanopores sequencing is a process of electrically sequencing DNA, nucleic acid and proteins. The present review gives a detailed account of various aspects of nanopore sequencing. Nanopore sequencing involves fabrication of nanopores followed by placing the nanopore in an electrolytic solution and applying electric potential to it. The applied electric field drives the immersed analyte to pass through the nanopore. Commonly, a sugar molecule is fixed at the pore entrance which traps the DNA molecule for a while so as to complete an electronic circuit. As soon as the DNA molecule gets trapped there is a characteristic change in the electric current depending on the kind of base A, G, C, or T, which represents a direct reading of the DNA sequence. The detection principle is based on monitoring the ionic current passing through the nanopore as a voltage is applied across the nanopore. This sequencing technique provides a wide range of applications in the fields of Biotechnology, Nanotechnology, Medical, Forensics etc.
Keywords: Synthetic nanopores